Malaysian Armed Forces Logistic Management Problem: The Effect to the Country’s Defence - Haris Mustapa; Saiful Bakri; Mohamed Faisol Keling; Mohd Ainuddin Iskandar Lee; Nazariah Osman (International Journal of Supply Chain Management, 2020)
The country’s military development is a need to the country to ensure its viability. With the development of threat that not only traditional threat but it changes to the non-traditional threats. The security threat has influence the country’s military development and Defence Policy. It also implicates Malaysia which actively developing the military after the Cold War in 1991. Between 1957 to 1991, Malaysia has been focusing to the threat in the country specifically the communist threat that affects the country’s safety and sovereignty. After the peace treaty between PKM and Malaysian government in 1989, Malaysia begins to actively developing the military. It is seen as a need for Malaysia to ensure the safety and defence of the country is in red alert to face any threat. However, in the rapid development of the military, there are some who see Malaysia is having problem to ensure the country’s readiness in facing the threat. With various negative issues being reported, it has raised question on the current status and the problem that Malaysia is facing in ensuring Malaysian Armed Forces (MAF) readiness. Therefore, this study touches the problem faced by the government and specifically MAF in logistics aspect that gives impact towards National Defence Policy (NDP).